Penerapan Metode Teorema Bayes Pada Sistem Pakar Dalam Mendeteksi Penyakit Lupus Erythematosus Menggunakan PHP - Fithry Tahel; Erwin Ginting (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
Systemic lupus erythematosus is a systemic autoimmune disease characterized by the presence of autoantibodies against autoantigens, formation of immune complexes, and dysregulation of the immune system, causing damage to several organs of the body. An expert system is an artificial intelligence application that connects a knowledge base with an inference system to imitate an expert. An expert system is a system that seeks to adopt human knowledge to computers so that computers can solve problems as is usually done by experts. or Systematic Lupus Erythomatosus is a lupus disease that attacks every vital organ in the human body such as the heart, lungs, kidneys, blood cell organs and joints. SLE is a type of lupus disease that is the most severe and difficult for every medical expert to overcome. A person with SLE will consume certain drugs. The goal to be achieved is to create an expert system application that is useful as a tool to obtain information and initial guesses in diagnosing SLE. The result of this study is that an expert system for diagnosing SLE by using the Bayes theorem method can solve the problem of diagnosing SLE based on the symptoms felt by answering questions such as consulting a doctor.Keywords: Expert System, Bayes' Theorem, SLE, Sistemik Autoimun